Fluorinated silane / attapulgite / copper-iron Prussian blue analogue / silver antibacterial hydrophobic coating as well as preparation method and application thereof

By using fluoride silane/concave and concave rock stone/copper-iron Prussian blue analog/silver nanocomposites, a coating with hydrophobic and antibacterial properties is formed, which solves the problems of corrosion, bacterial pollution and mold in cultural relics protection, and achieves efficient protection of cultural relics.

CN119570365AActive Publication Date: 2025-03-07SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411770895.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively protect cultural relics and prevent corrosion, bacterial contamination and mildew, and at the same time, it lacks a protective coating that has both hydrophobic and antibacterial properties.

Method used

Using fluoride silane/concave and concave rock stone/copper-iron Prussian blue analog/silver nanocomposite materials, a nanocomposite antibacterial hydrophobic protective coating for stone cultural relics with good hydrophobic properties and antibacterial properties is formed through ultrasonic dispersion and spray gun spraying technology.

Benefits of technology

It has achieved good hydrophobic properties and excellent antibacterial properties on the surface of cultural relics, avoided the breeding of bacteria and fungi, effectively protected cultural relics, and also had the advantages of low cost, safety and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570365A_ABST
    Figure CN119570365A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of cultural relic protection, and particularly relates to a preparation method of an antibacterial hydrophobic coating for stone cultural relic protection. According to the method, an attapulgite / copper-iron prussian blue analogue / silver nano composite material is synthesized by adopting a simple wet chemical method and an electrochemical replacement method, in the preparation process, natural nano rodlike mineral attapulgite is used as a carrier, and prussian blue analogue nano particles are loaded on the surface of the carrier by adopting an in-situ precipitation method; the antibacterial property of the natural mineral material is effectively improved; furthermore, nano Ag is used for modifying the Prussian blue analogue, so that the killing effect of the composite material on bacteria and fungi can be effectively enhanced, the photo-thermal performance of the Prussian blue analogue can be improved, and the purpose of long-acting bacteriostasis is achieved; and finally, carrying out hydrophobic treatment on the coating by using fluorinated silane to obtain the antibacterial hydrophobic self-cleaning coating for protecting the stone cultural relics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cultural relics protection, and specifically relates to a fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver antibacterial hydrophobic coating and a preparation method and application thereof. Background Art

[0002] China has a long history, and its traditional culture is even more profound. Looking back at the history of "China's five thousand years", countless cultural relics are like brilliant treasures, shining in the long river of history. As historical evidence, cultural relics are irreplaceable. At the same time, they themselves have inestimable important historical value, cultural value, scientific value, artistic value, and educational value. However, the damage, natural weathering, deliquescence, and mildew of cultural relics have always troubled countless scholars. Therefore, how to better preserve and pass on cultural relics has become the top priority of countless cultural relics protection scholars. There are few applications and research in this aspect in the prior art. Therefore, in view of the various effects of natural, humanistic and other environments on cultural relics, it is urgent to study a protective coating that can be applied to the surface of cultural relics without causing damage to the cultural relics and can achieve the purpose of "repairing the old as the old".

[0003] Attapulgite is a hydrous magnesium-rich silicate clay mineral with a layered chain structure. It contains a large number of pores, has a unique fiber morphology and porous structure, and is a natural mineral with multiple uses and high added value. It has certain similarities with stone cultural relics in structure and composition. Therefore, it is considered to use it to form a nano-composite antibacterial hydrophobic protective coating for the protection of stone cultural relics with good hydrophobic and antibacterial properties. It will be a new idea. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an antibacterial and hydrophobic coating for the protection of stone cultural relics, so as to solve the problems of cultural relic corrosion, bacterial contamination and mildew, and achieve good hydrophobic properties and excellent antibacterial properties. This technology has the advantages of low cost, safety and environmental protection.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating comprises the following steps:

[0007] Step 1, weigh a certain mass of ferric chloride, cupric chloride dihydrate, and attapulgite, disperse the two metal chlorides and attapulgite in a 1.0-5.0 mM citric acid aqueous solution, stir until the solution is uniformly dispersed, and ultrasonically disperse for 15-30 minutes to obtain solution A; weigh a certain mass of potassium ferrocyanide trihydrate, disperse it in a 1.0-5.0 mM citric acid aqueous solution, stir until the solution is uniformly dispersed, and ultrasonically disperse for 15-30 minutes to obtain solution B; transfer solution A to a constant temperature water bath heating pot, add solution B dropwise, react at a constant temperature for 2-10 minutes, move to room temperature, and continue stirring for 30 minutes; after the reaction is completed and cooled naturally, the obtained sample is centrifuged, and the solid precipitate is washed and dried to obtain an attapulgite / copper iron Prussian blue analog nanocomposite material;

[0008] Step 2: Weigh a certain amount of attapulgite / copper iron Prussian blue analog nanocomposite material and disperse it in deionized water, then add silver nitrate, stir for 2 hours, centrifuge, wash and dry the obtained composite material to obtain attapulgite / copper iron Prussian blue analog / silver nanocomposite material;

[0009] Step 3: Mix the attapulgite / copper iron Prussian blue analogue / silver nanocomposite material with 1H,1H,2H,2H-perfluorodecyltriethoxysilane in an ethanol aqueous solution, then ultrasonically disperse for 15 to 30 minutes and stir at room temperature for 2 to 10 hours; finally, spray the mixed solution on the sandstone cultural relic substrate with a spray gun to obtain a fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver antibacterial hydrophobic coating.

[0010] Furthermore, the mass ratio of ferric chloride, cupric chloride dihydrate and potassium ferrocyanide trihydrate added in the step 1 is 16:17:(30-72).

[0011] Furthermore, in the step 1, the amount of ferric chloride added is 8-32 g / L, and the amount of cupric chloride dihydrate added is 8.5-34 g / L.

[0012] Furthermore, in the step 1, the amount of potassium ferrocyanide trihydrate added is 21-84 g / L.

[0013] Furthermore, in the step 2, the addition amount of the attapulgite / Prussian blue analog nanocomposite material is 5-10 g / L.

[0014] Furthermore, in the step 2, the amount of silver nitrate added is 3.6-10 g / L.

[0015] Furthermore, in the step three, the amount of 1H,1H,2H,2H-perfluorodecyltriethoxysilane added is 10 mL / L, and the stirring time is 6 h.

[0016] A fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating prepared by any of the above preparation methods.

[0017] Furthermore, the modified Prussian blue analog nanoparticles are uniformly loaded on the surface of nanorod-shaped attapulgite, the length of the attapulgite is 200-500 nm, and the size of the Prussian blue analog nanoparticles is 5-50 nm.

[0018] An application of the above-mentioned fluorinated silane / attapulgite / copper-iron Prussian blue analogue / silver antibacterial hydrophobic coating in the protection of leather cultural relics, paper cultural relics, bamboo and wooden articles, and murals.

[0019] Compared with the prior art, the present invention has the following technical effects:

[0020] The invention uses natural nano-rod-shaped attapulgite mineral as a carrier, adopts a simple in-situ precipitation method and an electrochemical replacement method to synthesize a attapulgite / copper-iron Prussian blue analogue / silver nano-composite material, effectively solves the agglomeration problem of Prussian blue nano-materials, and improves the antibacterial property and commercial value of low-cost natural clay minerals; the composite of nano-Ag further improves the photothermal property of the nano-composite material, and improves the antibacterial activity and photothermal property of the nano-composite coating; the addition of 1H,1H,2H,2H-perfluorodecyltriethoxysilane can reduce the surface energy of the coating, complements the increased roughness of attapulgite, greatly improves the hydrophobic property of the coating, and forms a nano-composite antibacterial hydrophobic protective coating for stone cultural relics protection with good hydrophobic and antibacterial properties.

[0021] (1) In the present invention, the excellent aspect ratio of attapulgite improves the dispersibility of the nanomaterial and the roughness of the coating, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane reduces the surface energy of the coating. The two complement each other to ultimately obtain a hydrophobic coating with a contact angle of 165°.

[0022] (2) Attapulgite can effectively solve the agglomeration problem of Prussian blue analogues. The dissolution effect of iron ions, copper ions and silver ions in Prussian blue analogues jointly improves the antibacterial activity of the nanocomposite material, forming a hydrophobic antibacterial coating with good hydrophobic properties and excellent antibacterial properties. At the same time, the synergistic photothermal effect of silver nanoparticles and Prussian blue analogues further improves the antibacterial properties of the coating.

[0023] (3) The hydrophobic antibacterial coating prepared by the present invention has excellent performance, low price, safety, environmental protection and wide application range. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1From top to bottom are the XRD patterns of the attapulgite / copper iron Prussian blue analogue / silver (APT / CuFePBA / Ag) nanocomposite prepared in Example 1, the attapulgite / copper iron Prussian blue analogue (APT / CuFePBA) nanocomposite prepared in Comparative Example 1, the attapulgite / copper Prussian blue analogue (APT / CuPBA) nanocomposite, the attapulgite / Prussian blue (APT / PB) nanocomposite and attapulgite (APT);

[0025] Figure 2 TEM photo of the APT / CuFePBA nanocomposite prepared in Comparative Example 1;

[0026] Figure 3 TEM image of the APT / CuFePBA / Ag nanocomposite prepared in Example 1;

[0027] Figure 4 From top to bottom, the temperature changes of equal concentration APT, APT / CuFePBA and APT / CuFePBA / Ag nanocomposite solutions under xenon lamp irradiation are shown;

[0028] Figure 5 From left to right, the water contact angle tests of untreated sandstone, sandstone treated with fluorinated silane / attapulgite (Fluor / APT), and sandstone treated with Fluor / APT / CuFePBA / Ag are shown;

[0029] Figure 6 The effect of the amount of APT / CuFePBA / Ag nanocomposite added on the water contact angle of Fluor / APT / CuFePBA / Ag nanocomposite antibacterial hydrophobic coating;

[0030] Figure 7 This is a super-depth microscopic photograph of bacterial colony growth on the surface of untreated sandstone;

[0031] Figure 8 This is an ultra-depth microscopic photograph of bacterial colony growth on the sandstone surface sprayed with Fluor / APT coating;

[0032] Fig. 9 This is an ultra-depth-of-field microscope photo of the bacterial colony growth on the sandstone surface sprayed with Fluor / APT / CuFePBA / Ag nanocomposite antibacterial hydrophobic coating; DETAILED DESCRIPTION

[0033] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0034] Example 1

[0035] Step 1: First, weigh 0.64g of ferric chloride, 0.68g of cupric chloride dihydrate, and 1.69g of potassium ferrocyanide trihydrate, respectively, disperse the ferric chloride in 0.4g of attapulgite citric acid aqueous solution to obtain solution A, disperse potassium ferrocyanide in citric acid aqueous solution (2mM) to obtain solution B, stir until the two solutions are evenly dispersed, and then ultrasonically disperse for 30min; stir until the solution is evenly dispersed, ultrasonically disperse for 30min to obtain solution B; transfer solution A to a constant temperature water bath heating pot, add solution B dropwise, react at a constant temperature for 5min, move to room temperature, and continue stirring for 30min; finally, after the reaction is completed and cooled naturally, the obtained sample is centrifuged, and the precipitated solid is washed and dried to obtain an attapulgite / copper-iron Prussian blue analog nanocomposite material;

[0036] Step 2: Weigh 0.25 g of attapulgite / copper iron Prussian blue analogue and 0.17 g of silver nitrate respectively, disperse the attapulgite / copper iron Prussian blue analogue in deionized water and continue stirring, then add silver nitrate and stir for 2 hours, centrifuge, wash and dry the resulting composite material to obtain a attapulgite / copper iron Prussian blue analogue / silver nanocomposite material.

[0037] Step 3: Mix 0.2 g of attapulgite-silver-coated Prussian blue / copper Prussian blue analogue with 0.5 ml of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in 50 ml of ethanol solution, then ultrasonically disperse for 30 minutes, stir at room temperature for 6 hours, and spray the mixed solution on the substrate with a spray gun to obtain a fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver antibacterial hydrophobic coating.

[0038] Example 2

[0039] Step 1: First, weigh 0.64g of ferric chloride, 0.68g of cupric chloride dihydrate, and 1.69g of potassium ferrocyanide trihydrate, respectively, disperse the ferric chloride in 0.4g of attapulgite citric acid aqueous solution to obtain solution A, disperse potassium ferrocyanide in citric acid aqueous solution (2mM) to obtain solution B, stir until the two solutions are evenly dispersed, and then ultrasonically disperse for 30 minutes; transfer solution A to a constant temperature water bath heating pot, add solution B dropwise, react at a constant temperature for 5 minutes, move to room temperature, and continue stirring for 30 minutes; finally, after the reaction is completed and cooled naturally, the obtained sample is centrifuged, and the precipitated solid is washed and dried to obtain an attapulgite / copper iron Prussian blue analog nanocomposite material;

[0040] Step 2: Weigh 0.25 g of attapulgite / copper iron Prussian blue analogue and 0.25 g of silver nitrate respectively, disperse the attapulgite / copper iron Prussian blue analogue in deionized water and continue stirring, then add silver nitrate and stir for 2 hours, centrifuge, wash and dry the resulting composite material to obtain a attapulgite / copper iron Prussian blue analogue / silver nanocomposite material.

[0041] Step 3: Mix 0.2 g of attapulgite / copper iron Prussian blue analogue / silver with 0.5 ml 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in 50 ml ethanol solution, then ultrasonically disperse for 30 min, stir at room temperature for 6 h, and spray the mixed solution on the substrate with a spray gun to obtain a fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver antibacterial hydrophobic coating.

[0042] Example 3

[0043] Step 1: First, weigh 0.64g of ferric chloride, 0.68g of cupric chloride dihydrate, and 1.69g of potassium ferrocyanide trihydrate, respectively, disperse the ferric chloride in 0.4g of attapulgite citric acid aqueous solution to obtain solution A, disperse potassium ferrocyanide in citric acid aqueous solution (2mM) to obtain solution B, stir until the two solutions are evenly dispersed, and then ultrasonically disperse for 30 minutes; transfer solution A to a constant temperature water bath heating pot, add solution B dropwise, react at a constant temperature for 5 minutes, move to room temperature, and continue stirring for 30 minutes; finally, after the reaction is completed and cooled naturally, the obtained sample is centrifuged, and the precipitated solid is washed and dried to obtain an attapulgite / copper iron Prussian blue analog nanocomposite material;

[0044] Step 2: Weigh 0.25 g of attapulgite / copper iron Prussian blue analogue and 0.17 g of silver nitrate respectively, disperse the attapulgite / copper iron Prussian blue analogue in deionized water and continue stirring, then add silver nitrate and stir for 2 hours, centrifuge, wash and dry the resulting composite material to obtain a attapulgite / copper iron Prussian blue analogue / silver nanocomposite material.

[0045] Step 3: Mix 0.15 g of attapulgite / copper iron Prussian blue analogue / silver with 0.5 ml of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in 50 ml of ethanol solution, then ultrasonically disperse for 30 minutes, stir at room temperature for 6 hours, and spray the mixed solution on the substrate with a spray gun to obtain a fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver antibacterial hydrophobic coating.

[0046] Example 4

[0047] Step 1: First, weigh 0.64g of ferric chloride, 0.68g of cupric chloride dihydrate, and 1.69g of potassium ferrocyanide trihydrate, respectively, disperse the ferric chloride in 0.4g of attapulgite citric acid aqueous solution to obtain solution A, disperse potassium ferrocyanide in citric acid aqueous solution (2mM) to obtain solution B, stir until the two solutions are evenly dispersed, and then ultrasonically disperse for 30 minutes; transfer solution A to a constant temperature water bath heating pot, add solution B dropwise, react at a constant temperature for 5 minutes, move to room temperature, and continue stirring for 30 minutes; finally, after the reaction is completed and cooled naturally, the obtained sample is centrifuged, and the precipitated solid is washed and dried to obtain an attapulgite / copper iron Prussian blue analog nanocomposite material;

[0048] Step 2: Weigh 0.25 g of attapulgite / copper iron Prussian blue analogue and 0.17 g of silver nitrate respectively, disperse the attapulgite / copper iron Prussian blue analogue in deionized water and continue stirring, then add silver nitrate and stir for 2 hours, centrifuge, wash and dry the resulting composite material to obtain a attapulgite / copper iron Prussian blue analogue / silver nanocomposite material.

[0049] Step 3: Mix 0.1 g of attapulgite / copper iron Prussian blue analogue / silver with 0.5 ml of 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in 50 ml of ethanol solution, then ultrasonically disperse for 30 minutes, stir at room temperature for 6 hours, and spray the mixed solution on the substrate with a spray gun to obtain a fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver antibacterial hydrophobic coating.

[0050] Comparative Example 1

[0051] Step 1: Mix 0.2 g of attapulgite and 0.5 ml of 1H,1H,2H,2H-perfluorodecyltriethoxysilane in 50 ml of ethanol solution, then ultrasonically disperse for 30 minutes, stir at room temperature for 6 hours, and spray the mixed solution on the substrate with a spray gun to obtain a fluorinated silane / attapulgite hydrophobic coating.

[0052] Comparative Example 2

[0053] Step 1: First, weigh 0.64g of ferric chloride, 0.68g of cupric chloride dihydrate, and 1.69g of potassium ferrocyanide trihydrate, respectively, disperse the ferric chloride in 0.4g of attapulgite citric acid aqueous solution to obtain solution A, disperse potassium ferrocyanide in citric acid aqueous solution (2mM) to obtain solution B, stir until the two solutions are evenly dispersed, and then ultrasonically disperse for 30 minutes; transfer solution A to a constant temperature water bath heating pot, add solution B dropwise, react at a constant temperature for 5 minutes, move to room temperature, and continue stirring for 30 minutes; finally, after the reaction is completed and cooled naturally, the obtained sample is centrifuged, and the precipitated solid is washed and dried to obtain an attapulgite / copper iron Prussian blue analog nanocomposite material;

[0054] Figures 1 to 9 These are the characterization results of Fluor / APT / CuFePBA / Ag nanocomposite antibacterial hydrophobic coating. Figure 1 From top to bottom, the XRD patterns of the fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver (Fluor / APT / CuFePBA / Ag) nanocomposite prepared in Example 1, the attapulgite / copper iron Prussian blue analogue (APT / CuFePBA) nanocomposite prepared in Comparative Example 2, the attapulgite-copper Prussian blue analogue (CuPBA-APT) nanocomposite, the attapulgite-Prussian blue (PB-APT) nanocomposite and attapulgite (APT) are shown. All attapulgite-based composites clearly show the diffraction peak of attapulgite, which matches that of pure APT. In addition, an obvious PB characteristic peak (JCPDS 01-0239) appears in the XRD pattern of the PB-APT nanocomposite antibacterial agent. There is also a diffraction peak of silver oxide in the APT / CuFePBA / Ag spectrum, indicating that the APT / CuFePBA / Ag nanocomposite is successfully prepared.

[0055] Figure 2 TEM photo of the APT / CuFePBA nanocomposite prepared in Comparative Example 2. Figure 3 TEM image of APT / CuFePBA / Ag prepared in Example 1. Figure 2 and Figure 3 It can be seen that the natural mineral clay attapulgite has a nanorod-like structure with a length of 400-500nm and a width of about 10nm. It has a very large aspect ratio. It can be observed that there are a large number of nanoparticles on it, and they are relatively uniform. Combined with the XRD test results, it can be seen that they are PB and CuPBA nanoparticles. Figure 3 It can be observed that different from Figure 2 The nanoparticles are presumed to be some Ag2O nanoparticles, which further illustrates the successful preparation of Ag@PB / CuPBA-APT nanocomposites.

[0056] Figure 4 From top to bottom, the temperature changes of APT, APT / CuFePBA and APT / CuFePBA / Ag solutions with the same concentration under xenon lamp irradiation (room temperature 25°C); under xenon lamp irradiation for five minutes, the temperature of deionized water did not change significantly, while the temperature of APT / CuFePBA aqueous solution increased by 7.2°C. At the same time, the temperature of APT / CuFePBA / Ag aqueous solution increased by 11.9°C, and the photothermal effect was good;

[0057] Figure 5From left to right are the test results of water contact angle of untreated sandstone, sandstone sprayed with fluorinated silane / attapulgite (Fluor / APT) coating and Fluor / APT / CuFePBA / Ag nanocomposite antibacterial hydrophobic coating. The hydrophobic performance of sandstone is greatly improved after spraying with Fluor / APT and Fluor / APT / CuFePBA / Ag coating, and the contact angle reaches more than 165°. The roughness increased by the large aspect ratio of the APT nanocomposite material is an important factor in improving the hydrophobic performance of the coating.

[0058] Figure 6 This is the effect of APT / CuFePBA / Ag addition on the water contact angle of Fluor / APT / CuFePBA / Ag nanocomposite antibacterial hydrophobic coating. With the increase of Ag@PB / CuPBA-APT addition in the solution, the water contact angle of the coating gradually increases, reaching 162.11° at 0.2g, which once again illustrates that the large aspect ratio of the APT nanocomposite increases the roughness of the coating surface, thereby improving the water contact angle and hydrophobic properties of the coating.

[0059] Figures 7 to 9 These are ultra-depth-of-field microscope photos of colony growth on the surfaces of untreated sandstone, sandstone sprayed with Fluor / APT coating, and sandstone sprayed with Fluor / APT / CuFePBA / Ag nano-composite antibacterial and hydrophobic coating. After 7 days of culture with the mixed bacterial solution, it can be seen that the surface of the untreated sandstone is covered with hyphae; the hyphae on the surface of the sandstone sprayed with Fluor / APT coating are slightly reduced because the coating has good hydrophobic properties, making it difficult for bacteria and fungi to attach to the coating surface, but the coating does not have an antibacterial effect, so there are still more hyphae covering the surface; basically no hyphae can be observed on the surface of the sandstone sprayed with Fluor / APT / CuFePBA / Ag nano-composite antibacterial and hydrophobic coating. With the dual effects of hydrophobicity and antibacterial properties of the coating, it is extremely difficult for bacteria and fungi to grow on the coating, which effectively hinders the growth of bacteria and fungi and plays a good protective role for the sandstone.

[0060] The above are only preferred embodiments according to the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, various modifications and changes may be made according to the embodiments of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the embodiments of the present invention shall be included in the protection scope of the embodiments of the present invention.

Claims

1. A method for preparing a fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating, characterized in that: The following steps are involved: Step 1, weigh a certain mass of ferric chloride, cupric chloride dihydrate, and attapulgite, disperse the two metal chlorides and attapulgite in a 1.0-5.0 mM citric acid aqueous solution, stir until the solution is uniformly dispersed, and ultrasonically disperse for 15-30 minutes to obtain solution A; weigh a certain mass of potassium ferrocyanide trihydrate, disperse it in a 1.0-5.0 mM citric acid aqueous solution, stir until the solution is uniformly dispersed, and ultrasonically disperse for 15-30 minutes to obtain solution B; transfer solution A to a constant temperature water bath heating pot, add solution B dropwise, react at a constant temperature for 2-10 minutes, move to room temperature, and continue stirring for 30 minutes; after the reaction is completed and cooled naturally, the obtained sample is centrifuged, and the solid precipitate is washed and dried to obtain an attapulgite / copper iron Prussian blue analog nanocomposite material; Step 2: Weigh a certain amount of attapulgite / copper iron Prussian blue analog nanocomposite material and disperse it in deionized water, then add silver nitrate, stir for 2 hours, centrifuge, wash and dry the obtained composite material to obtain attapulgite / copper iron Prussian blue analog / silver nanocomposite material; Step 3: Mix the attapulgite / copper iron Prussian blue analogue / silver nanocomposite material with 1H,1H,2H,2H-perfluorodecyltriethoxysilane in an ethanol aqueous solution, then ultrasonically disperse for 15 to 30 minutes and stir at room temperature for 2 to 10 hours; finally, spray the mixed solution on the sandstone cultural relic substrate with a spray gun to obtain a fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver antibacterial hydrophobic coating.

2. The method for preparing the fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating according to claim 1, characterized in that: The mass ratio of ferric chloride, cupric chloride dihydrate and potassium ferrocyanide trihydrate added in the step 1 is 16:17:(30-72).

3. The method for preparing the fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating according to claim 1, characterized in that: In the step 1, the amount of ferric chloride added is 8-32 g / L, and the amount of cupric chloride dihydrate added is 8.5-34 g / L.

4. The method for preparing the fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating according to claim 1, characterized in that: In the step 1, the amount of potassium ferrocyanide trihydrate added is 21-84 g / L.

5. The method for preparing the fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating according to claim 1, characterized in that: In the step 2, the addition amount of the attapulgite / Prussian blue analog nanocomposite material is 5-10 g / L.

6. The method for preparing the fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating according to claim 1, characterized in that: The amount of silver nitrate added in step 2 is 3.6-10 g / L.

7. The method for preparing the fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating according to claim 1, characterized in that: In the step 3, the amount of 1H,1H,2H,2H-perfluorodecyltriethoxysilane added is 10 mL / L, and the stirring time is 6 h.

8. An antibacterial hydrophobic coating of fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver prepared by the preparation method according to any one of claims 1 to 7.

9. The fluorinated silane / attapulgite / copper iron Prussian blue analog / silver antibacterial hydrophobic coating according to claim 8, characterized in that: The modified Prussian blue analog nanoparticles are uniformly loaded on the surface of nanorod-shaped attapulgite, the length of the attapulgite is 200-500nm, and the size of the Prussian blue analog nanoparticles is 5-50nm.

10. Use of the fluorinated silane / attapulgite / copper iron Prussian blue analogue / silver antibacterial hydrophobic coating as claimed in claim 8 in the protection of leather cultural relics, paper cultural relics, bamboo and wooden articles, and murals.

Citation Information

Patent Citations

  • Preparing method and application of super hydrophobic coating with photothermal effect

    CN109796859A

  • Super-hydrophobic Prussian blue material as well as preparation method and application thereof

    CN116040654A

  • Graphene coated CuFe2S4 / CuS nano composite material as well as preparation method and application thereof

    CN116864648A

  • Hollow Prussian blue analogue-silver nanomaterial as well as preparation method and application thereof

    CN118252930A

  • Dehydrated prussian blue analogue with hydrophobic layer as well as preparation method and application of dehydrated prussian blue analogue

    CN118619304A

Cited By

  • Green synthesis of nano-silver-attapulgite composite material, preparation method thereof and application of nano-silver-attapulgite composite material in antibiosis and antibiofilm

    CN122538811A